Impaired expression of serine/arginine protein kinase 2 (SRPK2) affects melanoma progression - Caetano, Mônica Maria Magalhães; Moreira, Gabriela Alves; Silva, Maria Roméria da; Guimarães, Gabriela Rapozo; Santos, Leandro de Oliveira; Pacheco, Amanda de Ambrósio; Siqueira, Raoni Pais; Mendes, Flávia Carneiro; Marques Da Silva, Eduardo De Almeida; Junior, Abelardo Silva; Rangel Fietto, Juliana Lopes; Saito, Ângela; et al. (Frontiers in Genetics, 2022)
Melanoma is one of the most aggressive tumors, and its lethality is associated with the ability of malignant cells to migrate and invade surrounding tissues to colonize distant organs and to generate widespread metastasis. The serine/arginine protein kinases 1 and 2 (SRPK1 and SRPK2) are classically related to the control of pre-mRNA splicing through SR protein phosphorylation and have been found overexpressed in many types of cancer, including melanoma. Previously, we have demonstrated that the pharmacological inhibition of SRPKs impairs pulmonary colonization of metastatic melanoma in mice. As the used compounds could target at least both SRPK1 and SRPK2, here we sought to obtain additional clues regarding the involvement of these paralogs in melanoma progression. We analyzed single-cell RNA sequencing data of melanoma patient cohorts and found that SRPK2 expression in melanoma cells is associated with poor prognosis. Consistently, CRISPR-Cas9 genome targeting of SRPK2, but not SRPK1, impaired actin polymerization dynamics as well as the proliferative and invasive capacity of B16F10 cells in vitro. In further in vivo experiments, genetic targeting of SRPK2, but not SRPK1, reduced tumor progression in both subcutaneous and caudal vein melanoma induction models. Taken together, these findings suggest different functional roles for SRPK1/2 in metastatic melanoma and highlight the relevance of pursuing selective pharmacological inhibitors of SRPK2.